2001
DOI: 10.1136/fn.84.3.f177
|View full text |Cite
|
Sign up to set email alerts
|

Randomised controlled study of oral erythromycin for treatment of gastrointestinal dysmotility in preterm infants

Abstract: Aim-To evaluate the eVectiveness of oral erythromycin as a prokinetic agent for the treatment of moderately severe gastrointestinal dysmotility in preterm very low birthweight infants. Methods-A prospective, double blind, randomised, placebo controlled study in a tertiary referral centre of a university teaching hospital was conducted on 56 preterm infants (< 1500 g) consecutively admitted to the neonatal unit. The infants were randomly allocated by minimisation to receive oral erythromycin (12.5 mg/kg, every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 34 publications
3
80
0
Order By: Relevance
“…1 Procedural pain associated with prolonged intravenous hyperalimentation seems a minor issue when performed with proper anesthesia and analgesia. However, these infants can present with serious and even life-threatening complications that include liver dysfunction and bloodstream infections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 Procedural pain associated with prolonged intravenous hyperalimentation seems a minor issue when performed with proper anesthesia and analgesia. However, these infants can present with serious and even life-threatening complications that include liver dysfunction and bloodstream infections.…”
mentioning
confidence: 99%
“…However, these infants can present with serious and even life-threatening complications that include liver dysfunction and bloodstream infections. 1 Establishing enteral feeding is therefore a critical milestone during management of premature infants. As feeding intolerance in premature infants is mainly functional, prokinetic drugs have been used with increasing frequency in newborn infants.…”
mentioning
confidence: 99%
“…Our study demonstrated that erythromycin-treated infants had significantly fewer episodes of large residual gastric aspirates and were able to attain FEF more quickly, as noted in other. 24,26 Thus, we suggest that the use of an intermediate dose of oral erythromycin could significantly reduce the number of withheld feeds and the time of FEF. 23 The main limitation of our study was that it was underpowered.…”
Section: Discussionmentioning
confidence: 99%
“…7,17,18 One study found a significant benefit with high-dose erythromycin (12.5 mg/kg q.i.d) compared to placebo for treating feeding intolerance in preterm infants with birth weight <1,500 grams [13.5 (8-22) vs. 25 (16-33) days, respectively]. 5 Also, Madani et al reported that a significant benefit was found in preterm infants >32 weeks who took highdose erythromycin (12.5 mg/kg q.i.d) compared to placebo. 2 Similarly, Aly et al found a significant benefit in preterm infants >32 weeks [10.5 (4.1) vs. 16.3 (5.7) days, respectively, with low-dose erythromycin (1 mg/ kg t.i.d) compared to placebo.…”
Section: Discussionmentioning
confidence: 99%
“…This macrolide has a motilin-like effect and stimulates peristalsis. 1,5 Erythromycin works as a motiline agent, by binding to the motiline receptor at the antrum and upper duodenum and leading to increased contractions in the antrum. 4,6 The motiline hormone stimulates the gastric emptying process and induces phase III of migrating motor complexes (MMC) in the proximal intestine, reducing transit time in the intestine.…”
mentioning
confidence: 99%